(untitled) (Journal of the College of Basic Education, 2024)
The current research is summarized in main concept: The first is the moral orientation, which is the tendency of the individual to express his values ​​in situations that require a moral decision, and it is either a grammatical, effective, deliberative or emotional directive. 1- The moral orientation of university students 2- Differences in moral orientation according to Gender (male - female) and specialization (scientific - human). The current research is limited to students of Al-Mustansiriya University for morning study of both sexes (males - females) and for both disciplines (scientific - human) for the academic year (2020-2021). Translated in to Arabic by Al-Qaisi 2020, which consists of (28) paragraphs. tool were presented to a group of (15) arbitrators. The researcher. followed the correlative descriptive approach and applied the two tools to the research sample of (400) male and female students from Al-Mustansiriya University. After extracting the psychometric properties of the scale from the validity and reliability, as the apparent validity and construct validity were used for both scales, while the reliability was used for the moral orientation scale, the retest method was used. the absolute standard of the reliability coefficient by the retest method was (0.67) and by the Alpha Cronbach method it reached (0.81) and then they were applied to the research sample and the statistical treatments that fit with the nature and objectives of the research through the statistical package (SPSS) showed the following results : 1- University students have a moral orientation. 2- There are no statistically significant differences in moral orientation to the variable of gender and specialization. The results were interpreted according to the theories adopted, and the research concluded with several recommendations and suggestions which are